Selective depression of arsenopyrite with in situ generated nanoparticles in pyrite flotation. (1st November 2021) - Wang, Zhen; Cao, Jun; Wang, Li; Xiao, Junhui; Wang, Jinming
Graphical abstract: Highlights: Selective generation of ZnCO3 nanoparticles (ZCNPs) on arsenopyrite surface. Flotation of pyrite from arsenopyrite with ZCNPs as depressant. ZCNPs inhibit SBX adsorption thus depress arsenopyrite flotation. Abstract: In this study, the selective depression of arsenopyrite in pyrite flotation with in-situ generated nanoparticles was studied. Scanning electron microscope and energy dispersive X-ray spectroscopy (SEM/EDS) detection, solution chemistry analysis, fourier transform infrared spectroscopy (FTIR), adsorption tests and contact angle measurement were used to reveal the corresponding mechanism. Flotation results showed that arsenopyrite were selectively depressed and pyrite had a better flotability at pH 8.7. SEM/EDS results showed that Zn-containing nanoparticles are largely produced on arsenopyrite but rarely on the pyrite surface. Solution chemistry calculations showed that ZnCO3 nanoparticles were the major hydrophilic species at pH 7–9. This consists with the pH range where arsenopyrite was depressed. The selective generation of ZnCO3 nanoparticles on arsenopyrite surface was further confirmed by FTIR analysis. The ZnCO3 nanoparticles inhibited the adsorption of the collector onto arsenopyrite surface and made it more hydrophilic, which was suggested by the adsorption and contact angle measurement results. A model showing the selective depression mechanism of ZnSO4 on pyrite/arsenopyrite flotation system in Na2 CO3 solution was also proposed. The comminution process is worth further study to clarify that whether the selective formation of ZnCO3 nanoparticles on pyrite and arsenopyrite surface is due to the difference in surface roughness.